1967
DOI: 10.1080/00022470.1967.10468974
|View full text |Cite
|
Sign up to set email alerts
|

Urban Development in Air Pollution Basins: An Appeal to the Planners for Help

Abstract: The air basin between the Mississippi River and the bluff in Illinois is of particular interest for this report. The autumnal temperature profiles were measured by a wiresonde. Each day through September and October had an inversion at dawn and/or dusk. During the entire three months, inversions 5° or more occurred at dawn 64% of the mornings, those 10° or more occurred 45% of the mornings; and those 1 5°o ccurred 23% of the mornings. Under intense inversions, the topography holds cool air in the basin like wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This finding was consistent with Huang et al (2018), which examined the effects of urban land expansion on air pollution in China, and found that urban land expansion influenced air pollution, with a significant relationship to the concentration of air pollutants [55]. Zhang et al (2015) found that visibility was significantly affected by the variation of PMs concentrations [56], and many studies have also shown that forests can effectively reduce the concentration of PMs [15,29]. Therefore, the increase in the forest can effectively improve visibility, which was consistent with the results of this research.…”
Section: Relationships Between Lucc and Air Pollutants In The Referensupporting
confidence: 76%
See 1 more Smart Citation
“…This finding was consistent with Huang et al (2018), which examined the effects of urban land expansion on air pollution in China, and found that urban land expansion influenced air pollution, with a significant relationship to the concentration of air pollutants [55]. Zhang et al (2015) found that visibility was significantly affected by the variation of PMs concentrations [56], and many studies have also shown that forests can effectively reduce the concentration of PMs [15,29]. Therefore, the increase in the forest can effectively improve visibility, which was consistent with the results of this research.…”
Section: Relationships Between Lucc and Air Pollutants In The Referensupporting
confidence: 76%
“…On the contrary, land-use types, such as built-up land, can be associated with higher levels emissions of air pollution [3,14]. The idea that built-up land types have a significant impact on air quality has been proposed in the past [15,16], and has since been supported by several studies [17,18]. Zahari et al (2016) explored the relationship between built-up land and air quality in Malaysia, and the results showed that air quality can be manipulated or reduced through proper land use planning [19].…”
Section: Introductionmentioning
confidence: 99%
“…The other condition that aggravates the PM pollution is the existence of pollution-intensive factories near the city fringe, which was ever a symbol of modern industrial metropolitan megacities without zoning laws introduced in some countries. Another important factor that expedites PM buildup and worsens pollution level is the basin location of many cities such as Los Angeles, Chengdu, Urumqi, Mexico City, and Sydney, where polluted air is trapped beneath and within temperature inversion layers because of their particular geographic features [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%